Important Role of Mycorrhiza for Seed Germination and Growth of Dendrobium Orchids - Binti Tsulsiyah; Thoyibatul Farida; Cahya Lembayung Sutra; Endang Semiarti (Journal of Tropical Biodiversity and Biotechnology, 2021)
Indonesia is a tropical country that has natural forests and is suitable for orchid species habitat, leading to more than 5,000 species of orchids grow. The tropical area is the main distribution centre for epiphytic orchids, one of which is Dendrobium, which grows more than 1,000 species throughout the world. Orchid seeds are very small and do not have an endosperm, making germination difficult in their natural habitat. Mycorrhizal association with orchids plays a role in the survival of orchids in nature through seed germination and growth. This study aims to provide a deeper understanding about the important role of mycorrhiza in seed germination and growth of Dendrobium. The mechanism of mycorrhizal association with orchids begins with the initial contact of the fungus with the orchid, hyphae enter the cortex cells to form peloton, peloton lysis, and exchange of nutrients occurs. Orchid mycorrhiza that mostly found groups in Dendrobium are Rhizoctonia (Epulorhiza, Tulasnella, Rhizoctonia). Mycorrhiza plays a role in increased secretion of phytohormone and enzyme activity which supports seed germination and growth of orchids. Specific mycorrhizal data on orchids can be used as an effort for in-situ and ex-situ conservation of Indonesian orchids, including Dendrobium.